Fatal Case of Primary Cutaneous Aggressive T-Cell Lymphoma Switching From a CD4+ to a CD8+ Phenotype: Progressive Disease With Bexarotene and Romidepsin Treatment. (November 2016) - Johnson, William T.; Leeman-Neill, Rebecca J.; Patel, Parth; Ho, Jonhan; Grandinetti, Lisa M.; Jedrych, Jaroslaw; Craig, Fiona E.
Abstract : Abstract: A 77-year-old white male presented to the clinic with two isolated cutaneous tumors on his forehead. A cutaneous biopsy showed a focally folliculotropic CD4 + cutaneous lymphoma. The tumors were irradiated with a complete response, and he was started on oral bexarotene. He experienced localized cutaneous relapse 3 months into treatment. These new tumors now revealed a surprisingly CD8 + cytotoxic phenotype, but with the same clone. A systemic workup was negative. His regimen was switched to romidepsin, and he was treated with local radiation again. Another 3.5 months passed in remission until he developed widespread cutaneous tumors. Positron emission tomography/computed tomography revealed multifocal systemic disease involving his diaphragm, liver, distal duodenum, proximal jejunum, anterior chest wall including pectoral muscles, and lungs without significant adenopathy. He died a few days later. Given his full clinical and pathological course, he was given the diagnosis of an aggressive primary cutaneous T-cell lymphoma, unspecified.